ANALISIS SEMIOTIK DALAM PUISI “BURUNG HITAM” KARYA W.S RENDRA - Devannia Putri Rizky; Wikanengsih Wikanengsih; Via Nugraha (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
Poetry is an expression of the soul through beautiful words. Poetry can motivate any reader who wants to know the meaning of the meaning implied in a poem through analysis. With this, the authors are interested in conducting research by analyzing the poem by W.S Rendra, entitled "Burung Hitam" using a semiotic approach. Semiotics is an approach that examines science in studying the signs contained in a literary work. Semiotics has a very important role in building a poem so that it can provide an overview and understanding to the reader. The purpose of this study, namely to analyze the meaning and describe the results of the analysis of the poetry semiotics. W.S Rendra's poem "Burung Hitam" packs his poetry freely with figurative words. The poem "Burung Hitam" is analyzed and discussed semiotically in order to find out about the meanings and linguistic signs contained in the poem. The method in this research is descriptive which analyzes the meaning content of the poem "Burung Hitam" which is studied semiotics which is an approach in studying the signs in a poem. The result of semiotic analysis research on the poem "Burung Hitam" means that there is a relationship between a marker and a marker by describing a love from the poet to his idol who is very strong and is equipped with a loyalty that is mysterious in nature or kept secret as a sign (signified) with the sign. (signifier).